Public opinion in policy contexts. A comparative analysis of domestic energy policies and individual policy preferences in Europe. Issue 1 (January 2021) - Stadelmann-Steffen, Isabelle; Eder, Christina
Recent research and real-world processes suggest that effective climate change mitigation policies are not feasible without at least a certain degree of public support. Hence, we investigate the link between existing domestic energy policies and individual policy instrument preferences in 21 European countries. We assume a policy feedback perspective and, thus, start from the idea that the current domestic energy context influences what future policies are possible and preferred by citizens. High political trust and strong climate change attitudes are expected to strengthen this relationship. Our results do not lend support to a general link between existing policies and future policy preferences. However, we find evidence of a positive policy feedback in individuals with strong climate change attitudes and/or high levels of political trust, which, depending on each country's current energy policy, either hinders or facilitates the energy transition.